Penerapan Inverse Manufacturing dalam Penanganan Produk Lampu Hemat Energi - Romy Loice; Bagus Made Arthaya; Harry Prasetyo (Jurnal Rekayasa Sistem Industri, 2016)
Lighting is one of the human basic needs that must be fullfiled. Compact fluorescent lamps is the most used lamp as source of lighting. However, they contain mercury, which is classified as heavy metals, that can potentially harm the environment. Even as mercury container, many people didn't know that. Many people don't know the method to handle the broken or used compact fluorescent lamp. They just dispose the broken compact fluorescent lamp to trash without considering the effect of mercury contained.